Justice and remembrance - "Shah-Kaxemi, Reza" (London, 2006)
Ali b. Abi Talib--son-in-law and cousin of the prophet Muhammad, first Shi'i imam and fourth caliph--is a monumental figure within the Islamic tradition. This book is the first serious engagement in English with the intellectual principles underpinning his teachings. The book focuses particularly on the spiritual and ethical content of his teachings and evaluates Ali's sacred conception of justice, while exploring the intimate connections between Ali's teachings and later Sufi doctrines.
Keywords: Islamic religion